2021
DOI: 10.1101/2021.07.18.452621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The balance of mitochondrial fission and fusion in cortical axons depends on the kinases SadA and SadB

Abstract: Neurons are highly polarized cells that display characteristic differences in the organization of their organelles in axons and dendrites. Mitochondria are of particular importance for neuronal homeostasis due to their high metabolic demand. The kinases SadA and SadB (SadA/B) promote the formation of distinct axonal and dendritic extensions during the development of cortical and hippocampal neurons. Here, we show that SadA/B are required for the axon-specific dynamics of mitochondria. The interaction with Anky… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that the activities of SAD-A/B and NUAK1 and their upstream kinase LKB1 are strongly biased in the axon and regulate axon specification and branching 39,40 . The SAD kinase has been shown to regulate the fission/fusion balance of mitochondria through phosphorylation of tau in the axon 51,52 . In contrast, we demonstrate that AMPK overactivation and suppression alters mitochondrial fission, and those changes are seen only in dendrites but not in the axon (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the activities of SAD-A/B and NUAK1 and their upstream kinase LKB1 are strongly biased in the axon and regulate axon specification and branching 39,40 . The SAD kinase has been shown to regulate the fission/fusion balance of mitochondria through phosphorylation of tau in the axon 51,52 . In contrast, we demonstrate that AMPK overactivation and suppression alters mitochondrial fission, and those changes are seen only in dendrites but not in the axon (Fig.…”
Section: Discussionmentioning
confidence: 99%